Meningkatkan Pemakaian Bahasa Inggris Tingkat Anak-Anak Di Keluarahan Patam Lestari - Andy Lau; Windi Afdal; Haeruddin Haeruddin (National Conference for Community Service Project (NaCosPro), 2019)
In this era, English is the most used in this world, cause of its best kwown can said that english is very important for us and for the next generation. The purpose of the community service for public is teaching, inform and socialization about the important of English for the children under 12th in Kelurahan Patam Lestari RW.006. The method we used in this program is Transfer knowledge to the children. The program well done just within 1day at Saturday 13.00 wib until 17.00 wib in RW006. The program held by 8 person (members) of our group. Through the activity showed good results such as the children know more about vocabulary and the already can introduces themselves in English. From that we can know that the children is acceptable, appreciate and intention about our program of learning English.